2015
DOI: 10.1152/ajpendo.00586.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of PPARβ/δ adversely affects satellite cells and reduces postnatal myogenesis

Abstract: Peroxisome proliferator-activated receptor β/δ ( PPARβ/δ) is a ubiquitously expressed gene with higher levels observed in skeletal muscle. Recently, our laboratory showed (Bonala S, Lokireddy S, Arigela H, Teng S, Wahli W, Sharma M, McFarlane C, Kambadur R. J Biol Chem 287: 12935–12951, 2012) that PPARβ/δ modulates myostatin activity to induce myogenesis in skeletal muscle. In the present study, we show that PPARβ/δ-null mice display reduced body weight, skeletal muscle weight, and myofiber atrophy during post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The specific ablation of PPARβ/δ in the mouse satellite cells has been reported, with approximately 40% fewer satellite cells than their wild-type littermates [ 156 ]. A similar observation was also reported in total PPARβ/δ-knock out mice [ 157 ]. Mice with PPARβ/δ-deficient muscle progenitor cells exhibited impaired muscle regeneration after cardiotoxin-induced injury and exhibited reduced growth kinetics and proliferation in primary cultures [ 156 ].…”
Section: Regulation Of Skeletal Muscle Regeneration By Pparssupporting
confidence: 87%
See 1 more Smart Citation
“…The specific ablation of PPARβ/δ in the mouse satellite cells has been reported, with approximately 40% fewer satellite cells than their wild-type littermates [ 156 ]. A similar observation was also reported in total PPARβ/δ-knock out mice [ 157 ]. Mice with PPARβ/δ-deficient muscle progenitor cells exhibited impaired muscle regeneration after cardiotoxin-induced injury and exhibited reduced growth kinetics and proliferation in primary cultures [ 156 ].…”
Section: Regulation Of Skeletal Muscle Regeneration By Pparssupporting
confidence: 87%
“…Mice with PPARβ/δ-deficient muscle progenitor cells exhibited impaired muscle regeneration after cardiotoxin-induced injury and exhibited reduced growth kinetics and proliferation in primary cultures [ 156 ]. Furthermore, these mice developed metabolic syndrome upon aging, similar to the PPARβ/δ knockout mice [ 43 , 156 , 157 ]. The authors found reduced foxhead box protein (FOXO1) expression in quiescent PPARβ/δ-deficient satellite cells, which impaired the proliferation and differentiation ability of these satellite cells during muscle regeneration, thus suggesting that PPARβ/δ regulates the regenerative capability of skeletal muscle through FOXO1 [ 156 ].…”
Section: Regulation Of Skeletal Muscle Regeneration By Pparsmentioning
confidence: 99%
“…1b ). It is interesting to note that several genes related with PPAR signaling pathway, such as PCK1, FABP4, SCD, PLIN1, ADIPOQ, MSTN, showed a higher expression in the concave side of the paravertebral muscles, since PPAR signaling pathway plays a major regulatory role in postnatal myogenesis and muscle fiber type (Wang et al 2004 ; Chandrashekar et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, we analyzed the role of Anx A1 in myoblast fusion in vivo during the initial days of the post-injury muscle regeneration. Published reports on muscle regeneration quantify this process by monitoring the following: a) expression of different myogenic differentiation markers at different times post-injury 43 ; b) the size of unregenerated (necrotic) areas in the muscle section 44 , and the number of newly formed (regenerated) myofibers 45 . In addition to employing all of these metrics, to specifically assess the extent of cell-cell fusion without being affected by the proliferation and myogenic commitment of the satellite cells, we also used a combination of different end points to assess myoblast differentiation and fusion.…”
Section: Discussionmentioning
confidence: 99%